Haemostasis biomarkers and risk of intracerebral haemorrhage in the REasons for Geographic and Racial Differences in Stroke Study - Zakai, Neil A.; Olson, Nels C.; Judd, Suzanne E.; Kleindorfer, Dawn O.; Kissela, Brett M.; Howard, George; Cushman, Mary (Thrombosis and Haemostasis, 2017)
Pathologic alterations in haemostasis cause bleeding disorders, but it is unknown if variation within the normal range relates to intracerebral haemorrhage (ICH) risk. It was our objective to assess the prospective associations of haemostasis biomarkers with ICH risk. The REasons for Geographic and Racial Differences in Stroke study (REGARDS) recruited 30,239 U. S. individuals aged ≥45 years. ICH was ascertained through biannual telephone contact and review of deaths followed by medical record evaluation. Haemostasis biomarkers (factor VIII (FVIII), factor IX (FIX), factor XI (FXI), fibrinogen, protein C, and D-dimer) were measured in a case cohort study consisting of ICH and a 1,104 person cohort random sample. The hazard ratio (HR) and 95 % confidence interval (CI) by biomarker were estimated using Cox models and adjusted for ICH risk factors. Individuals with a prior history of stroke, ICH or on warfarin were excluded. Over a median 5.8 years 66 ICH occurred. Fibrinogen, FVIII, FXI, and protein C were not associated with ICH risk in any analysis. Lower FIX increased risk of ICH with the bottom versus the top tertile of FIX associated with an HR of 5.68 (95 % CI 2.30, 14.05). D-dimer demonstrated a non-linear relationship with a potential threshold effect with increased risk only in the top 5th percentile (HR 3.22; 95 % CI 1.01, 10.31; pnon-linear = 0.04).In conclusion, low FIX levels within the normal range were associated with increased ICH risk. These data suggest non-pathologic alterations in haemostasis impact intracranial bleeding risk.
Keywords: Cerebral haemorrhage; cohort studies; continental population groups; epidemiology; haemostasis